Eco Fashion - Brown, Sass (Laurence King Publishing, 2010)
This title shows the range of companies making a difference in the area of sustainable design in fashion, exploding the myth that sustainable design is bad design, or at best basic design, by highlighting the range of companies producing desirable and well-designed apparel and accessories with a conscience.--from the Publisher